Navigating Multiple Roles: Communication Strategies of Indonesian Postgraduate Women in a Patriarchal Collectivist Culture - Kusumaningtyas, Shela; Hadinata, Wawan; Iman, Nur; Alinda, Yunati; Nurhaliza, Adinda Aulia; Nindyasari, Leoni (JURNAL KOMUNIKASI INDONESIA, 2026)
This study examines how Indonesian postgraduate women negotiate simultaneous roles as wives, mothers, workers, and students within a patriarchal collectivist culture. Using a qualitative case study with a constructivist orientation, the research focuses on six postgraduate students at the University of Indonesia who were selected through purposive criteria because they simultaneously managed family, work, and academic responsibilities. Data were collected through in-depth interviews, limited contextual observation, and supporting documents, and were analyzed using open, axial, and selective coding procedures. The findings show that role conflict is experienced not merely as a matter of time management, but as a layered burden involving moral expectations of motherhood, physical fatigue, guilt, and emotional spillover across domestic, professional, and academic domains. Interpersonal communication emerges as a central mechanism for negotiating boundaries, mobilizing support, and maintaining relationships with spouses, children, extended family, supervisors, colleagues, and lecturers. Intrapersonal communication, particularly self-talk and self-reflection, also plays a role in helping participants regulate emotion and sustain motivation. This study argues that communication functions not only as a coping tool, but also as a social process through which women manage caregiving responsibilities, pursue educational aspirations, and renegotiate gendered expectations in everyday life.